Development of second-order theory of mind: Assessment of environmental influences using a dynamic system approach. (May 2019) - Papera, Massimiliano; Richards, Anne; van Geert, Paul; Valentini, Costanza
Theory of mind refers to the ability to attribute beliefs to oneself and others. The present study used a dynamic systems approach to assess how environment may affect the development of second-order theory of mind (e.g., "John knows that Mary knows that he went out yesterday"). Theory of mind is divided into two major dimensions: comprehension (i.e., to understand a mental state) and prediction (i.e., to predict someone else's future behavior or mental state). Two age groups were assessed: 5–6- and 10–11-year-old children. In both age groups, participants were assigned to a condition of "support" (help provided) or "no support" (help not provided). Results show that second-order theory of mind follows a dynamic growth law that depends on support. Support facilitates performance in theory of mind production (i.e., to predict one's future behavior) for both the 5–6- and 10–11-year-old children. Interestingly, the 5–6-year-olds who received support presented an increase in the second-order prediction performance at the expense of the second-order comprehension, suggesting that a temporary dip in comprehension performance may facilitate the development of mental rules to predict one's future behavior.